A 3D hybrid‐shot spiral sequence for hyperpolarized 13C imaging. Issue 2 (7th September 2020) - Tyler, Andrew; Lau, Justin Y. C.; Ball, Vicky; Timm, Kerstin N.; Zhou, Tony; Tyler, Damian J.; Miller, Jack J.
Abstract : Purpose: Hyperpolarized imaging experiments have conflicting requirements of high spatial, temporal, and spectral resolution. Spectral‐spatial RF excitation has been shown to form an attractive magnetization‐efficient method for hyperpolarized imaging, but the optimum readout strategy is not yet known. Methods: In this work, we propose a novel 3D hybrid‐shot spiral sequence which features two constant density regions that permit the retrospective reconstruction of either high spatial or high temporal resolution images post hoc, (adaptive spatiotemporal imaging) allowing greater flexibility in acquisition and reconstruction. Results: We have implemented this sequence, both via simulation and on a preclinical scanner, to demonstrate its feasibility, in both a 1 H phantom and with hyperpolarized 13 C pyruvate in vivo. Conclusions: This sequence forms an attractive method for acquiring hyperpolarized imaging datasets, providing adaptive spatiotemporal imaging to ameliorate the conflict of spatial and temporal resolution, with significant potential for clinical translation.